Efeito da adição de nanopartículas de hexametafosfato de sódio em dentifrícios fluoretados sobre a desmineralização dentária: estudo in vitro - Nunes, Gabriel Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This study evaluated the effect of toothpastes containing 1100 ppm F associated with nano-sized sodium hexametaphosphate (HMPnano) on enamel demineralization in vitro, using a pH-cycling model. Design: Bovine enamel blocks (4 mm x 4 mm, n=72) selected by initial surface hardness (SHi) were randomly allocated into six groups (n=12), according to the test toothpastes: without fluoride or HMPnano (Placebo), 550 ppm F (550F), 1100 ppm F (1100F), 1100F plus HMPnano at concentrations of 0.25% (1100F/0.25%HMPnano), 0.5% (1100F/0.5%HMPnano), and 1.0% (1100F/1.0%HMPnano). Blocks were treated 2x/day with slurries of toothpastes and submitted to five pH cycles (demineralizing/remineralizing solutions) at 37 °C. Next, final surface hardness (SHf), integrated loss subsurface hardness (ΔKHN), integrated mineral loss (gHAp×cm-3) and enamel fluoride (F) concentration were determined. Data were analyzed by ANOVA and Student-Newman-Keuls‟ test (p < 0.001). Results: Toothpaste with 1100F/0.5%HMPnano led to the lowest mineral loss and the highest mineral concentration among all groups, which were 26% (SHf) and 21% (ΔKHN) lower and ~58% higher (gHAp×cm-3) when compared to 1100F (p < 0.001). Similar values of enamel F were observed for all fluoridated toothpastes (p > 0.001). Conclusion: The addition of 0.5%HMPnano to a 1100F toothpaste significantly enhances its effects against enamel demineralization when compared to its counterpart without HMPnano in vitro. Clinical Significance: Toothpaste containing 1100 ppm F associated with HMPnano has a higher potential to reduce the demineralization compared to 1100 ppm F. This toothpaste could be a viable alternative to patients at high risk of caries

Este estudo avaliou o efeito de dentifrícios contendo 1100 ppm F associado a nanopartículas de hexametafosfato de sódio (HMPnano) sobre a desmineralização do esmalte in vitro, utilizando um modelo de ciclagem de pH. Desenho: Blocos de esmalte bovino (4 mm x 4 mm, n=72) selecionados pela dureza de superfície inicial (SHi), foram alocados em seis grupos (n=12), de acordo com os dentifrícios teste: sem flúor ou HMPnano (Placebo), 550 ppm F (550F), 1100 ppm F (1100F), 1100F acrescido de HMPnano nas concentrações de 0,25% (1100F/0,25%HMPnano), 0,5% (1100F/0,5%HMPnano), e 1,0% (1100F/1,0%HMPnano). Blocos foram tratados 2x/dia com suspensões de dentífricios e submetidos a cinco ciclagens de pH (soluções desmineralizante/remineralizante) a 37 °C. A seguir, dureza de superfície final (SHF), perda integrada de dureza de subsuperfície (ΔKHN), concentração mineral (gHAp×cm-3) e concentração de fluoreto (F) no esmalte foram determinadas. Os dados foram submetidos à ANOVA seguido pelo teste Student-Newman-Keuls (p < 0,001). Resultados: Dentifrício com 1100F/0,5%HMPnano levou à menor perda mineral e maior concentração mineral em relação aos demais grupos (p < 0,001), que foram de 26% (SHF) e 21% (ΔKHN) inferior e ~ 58% maior (gHAp × cm-3) quando comparado ao 1100F (p < 0,001). Foram observados valores similares de F no esmalte para todos os dentifrícios fluoretados (p > 0,001). Conclusão: A adição de 0,5%HMPnano ao dentifrício 1100F aumenta significativamente os seus efeitos anticárie quando comparado com o seu equivalente sem HMPnano
Keywords: Desmineralização do dente; Esmalte dentário; Dentifrícios; Fosfatos; Nanopartículas; Tooth demineralization